Effectiveness Of Pt Good Doctor Technology Indonesia's Partnership Strategy And Communication Pattern With Partner Companies - Arif Wihananto; Akrom Arroisi; Silmi Kafa Hanifa Azzahra (Journal of Social Research, 2024)
This research discusses how the strategy and pattern of partnership communication carried out by PT Good Doctor Technology Indonesia with various forms of companies in order to provide telemedicine health services to all Indonesian people. With this research, it also has a goal to know and understand how the strategy and communication pattern are implemented, in order to worship the vision of PT Good Doctor Technology Indonesia, namely "1 (one) doctor for every Indonesian family". This research was conducted in a qualitative descriptive manner by conducting interviews with both internal and expert sources, in addition to conducting literature reviews and observations. In addition, the data and information obtained from this research were obtained from several ways of interviews, literature studies, and conservation. For resource persons, interviews were conducted with the business development & partnership team of Good Doctor, in addition to observing the business processes carried out by Good Doctor management, especially activities carried out by Good Doctor management towards its partner companies. This research provides information on the form of partnership business processes run by PT Good Doctor Technology Indonesia by providing benefits not only in 1 (one) party, but in all parties involved in the partnership, including the Indonesian people, especially users of telemedicine services